Macrophage Ferroptosis Promotes MMP2/9 Overexpression Induced by Hemin in Hemorrhagic Plaque - Li, Bicheng; Lu, Minqiao; Wang, Hui; Sheng, Siqi; Guo, Shuyuan; Li, Jia; Tian, Ye (Thrombosis and Haemostasis, 2023)
Background Intra-plaque hemorrhage (IPH) leads to rapid plaque progression and instability through upregulation of matrix metalloproteinases (MMPs) and collagen degradation. Hemoglobin-derived hemin during IPH promotes plaque instability. We investigated whether hemin affects MMP overexpression in macrophages and explored the underlying mechanisms.Material and Methods In vivo, hemorrhagic plaque models were established in rabbits and ApoE−/− mice. Ferrostatin-1 was used to inhibit ferroptosis. Plaque size, collagen, and MMP2/9 levels were evaluated using immunohistochemistry, H&E, Sirius Red, and Masson staining. In vitro, mouse peritoneal macrophages were extracted. Western blot and ELISA were used to measure MMP2/9 levels. Bioinformatics analysis investigated the association between MMPs and ferroptosis pathway genes. Macrophage ferroptosis was assessed by evaluating cell viability, lipid reactive oxygen species, mitochondrial ultrastructure, iron content, and COX2 levels after pretreatment with cell death inhibitors. Hemin's impact on ferroptosis and MMP expression was studied using Ferrostatin-1 and SB202190.Results In the rabbit hemorrhagic plaques, hemin deposition and overexpression of MMP2/9 were observed, particularly in macrophage-enriched regions. In vitro, hemin induced ferroptosis and MMP2/9 expression in macrophages. Ferrostatin-1 and SB202190 inhibited hemin-induced MMP2/9 overexpression. Ferrostatin-1 inhibited p38 phosphorylation in macrophages. Ferostatin-1 inhibits macrophage ferroptosis, reduces MMP2/9 levels in plaques, and stabilizes the hemorrhagic plaques.Conclusion Our results suggested that hemin-induced macrophage ferroptosis promotes p38 pathway activation and MMP2/9 overexpression, which may play a crucial role in increasing hemorrhagic plaque vulnerability. These findings provide insights into the pathogenesis of hemorrhagic plaques and suggest that targeting macrophage ferroptosis may be a promising strategy for stabilizing vulnerable plaque.
Keywords: intra-plaque hemorrhage; ferroptosis; macrophage; hemin; matrix metalloproteinases